Covid-19 Infection Complicated with Aortic Thrombosis: A Case Report - Islam, Md Zakirul; Ara, Anjuman; Fatema, Kaniz; Anne, Rifat Taher; Rahman, Md Mostafizur; Hussain, Mohammad Enayet; Yusuf, Md Abdullah (Journal of National Institute of Neurosciences Bangladesh, 2020)
Thromboembolic complications are well recognized events in Covid-19 infection. Most of the case fatalities are due to this event. Although any blood vessels may be involved, larger vessels are less commonly involved in this process. Here we describe a case of thrombosis of the arch of the aorta in association of Covid-19 infection in a hospitalized patient. The aim was to ensure timely identification and therapeutic intervention to prevent distal thromboembolic sequelae. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 143-145